Autophagic flux modulates tumor heterogeneity and lineage plasticity in SCLC - Hao, Yujie; Li, Mingchen; Liu, Wenxu; Ma, Zhenyi; Liu, Zhe (Frontiers in Oncology, 2025)
IntroductionSmall cell lung cancer (SCLC) is characterized by significant heterogeneity and plasticity, contributing to its aggressive progression and therapy resistance. Autophagy, a conserved cellular process, is implicated in many cancers, but its role in SCLC remains unclear.MethodsUsing a genetically engineered mouse model (Rb1fl/fl; Trp53fl/fl; GFP-LC3-RFP-LC3△G), we tracked autophagic flux in vivo to investigate its effects on SCLC biology. Additional in vitro experiments were conducted to modulate autophagic flux in NE and non-NE SCLC cell lines.ResultsTumor subpopulations with high autophagic flux displayed increased proliferation, enhanced metastatic potential, and neuroendocrine (NE) characteristics. Conversely, low-autophagic flux subpopulations exhibited immune-related signals and non-NE traits. In vitro, increasing autophagy induced NE features in non-NE cell lines, while autophagy inhibition in NE cell lines promoted non-NE characteristics.DiscussionThis study provides a novel model for investigating autophagy in vivo and underscores its critical role in driving SCLC heterogeneity and plasticity, offering potential therapeutic insights.